Evaluation and treatment of depression in dementia - Cristina, Davide (International Journal of Research in Medical Sciences, 2025)
Depression in later life is common with depressive symptoms present in 15% of all older adults and is often associated with coexisting chronic medical conditions, cognitive dysfunction or both. Although the depressive in later life conduction frequently manifests subthreshold symptoms such as not to satisfy the diagnostic criteria of DSM V, depression in the course of dementia should not be underestimated. The clinical features of depression associated with dementia vary from dysthymia-type psychopathological conditions to major depressive forms. Scientific evidence leans towards depression, not only as a comorbidity occurring in the various forms of dementia but as a significant contributor to the dementia etiopathogenesis. Depression in later life can be a prodrome, risk factor, comorbidity or consequence of mild cognitive impairment and dementia. In clinical practice in patients with dementia it is necessary to distinguish depression from apathy which is very frequent and overlaps with depression. Treatment of the psychological behavioural symptoms of dementia (BPDS), including depression, should initially be addressed non-pharmacologically with integrated management, as indicated by several guidelines as a first-line treatment approach except in emergency situations or severity.